The Strategy of The Head of Madrasah in Improving Teacher Professionalism - Khoirudin; Abu Darim; Muhammad Husnur Rofiq (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
A madrasah head must be able to develop a strategy by analyzing several things, including analyzing strengths, weaknesses, opportunities and threats. In this case, there is a link between teacher professionalism and the madrasa head. A madrasa principal needs the right and correct and effective strategy in carrying out his duties as a leader in an educational institution. The purpose of the research is the strategy for planning, implementing, supervising the head of the madrasa in increasing teacher professionalism at MA NU Sunan Ampel Baujeng Beji, Pasuruan Regency as well as the obstacles and completion of the headmaster's management strategy in increasing teacher professionalism in the school. The researcher used a qualitative type of research to describe the field and its relevance to the management strategy of the madrasa principal at MA NU Sunan Ampel Baujeng Beji, Pasuruan Regency.The results of the research above explain the context of efforts to improve teacher professionalism at MA NU Sunan Ampel Baujeng, concepts and strategic plans are needed to develop quality madrasas. Is a response to the need for quality Islamic educational institutions a struggle. The strategic plan carried out by MA NU Sunan Ampel Baujeng is by increasing teacher human resources such as participating in seminars, training, KKG, improving teacher welfare, providing supporting facilities such as the internet assisted by the deputy head of the madrasah and all elements in the madrasah.